Analysis of Demographic Factors Affecting Exclusive Breastfeeding Success among Breastfeeding Mothers - Indrasari, Nelly; Mugiati; Nurlaila; Warjidin Aliyanto; Indah Trianingsih (Jurnal Kesehatan, 2024)
Successful breastfeeding significantly impacts the health of both mothers and infants. This study aims to analyze factors affecting breastfeeding success through a quantitative design incorporating bivariate and multivariate analyses. Data were collected from 90 breastfeeding mothers and analyzed using statistical tests. The results reveal that maternal age is a significant factor (p-value=0.007); mothers aged 20–35 are 1.6 times more likely to breastfeed successfully than those younger than 20 or older than 35. Maternal education also plays a critical role (p-value=0.002); mothers with higher education levels are 2.3 times more likely to succeed in breastfeeding than those with primary education. Employment status is another significant factor (p-value=0.013); non-working mothers are 1.8 times more likely to breastfeed successfully than working mothers. Parity also influences success (p-value=0.029); multiparous mothers are 1.2 times more likely to succeed than primiparous mothers. These findings highlight the need for targeted interventions. Educational programs should prioritize mothers with primary or secondary education and those employed. Support mechanisms for working and primiparous mothers are crucial to address breastfeeding challenges. Policies such as extended maternity leave and workplace lactation facilities are also recommended to foster breastfeeding success. In conclusion, maternal age, education, employment status, and parity significantly impact breastfeeding outcomes. Tailored programs and supportive policies can improve breastfeeding rates and enhance maternal and infant health.